Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada PT Kereta Api Indonesia (PERSERO) dan Anak Perusahaan - Samsul Arifin; Liduina Asih Primandari (STIE Malangkucecwara, 2015)
Mobility of high society have become everyday activities. Smooth mobility requires a reliable transport and means. One of the widely used mass transportation Railway is operated by PT Kereta Api Indonesia. Even PT Kereta Api Indonesia has no competition in the rail transport business, but still need a good performance. The survival of the company is very important for the community, because rail transport is very affordable, especially for poor people. In this research, analysis of financial statements to determine the financial performance at PT Kereta Api Indonesia (Persero) and its subsidiaries based on the ratio of profitability. Profitabilias ratios include: gross profit margin (gross profit margin), the net profit margin (net profit margin), return on investment (ROI) and return on equity (ROE). The results of the analysis of financial statements found that PT Kereta Api Indonesia has a very good performance. These conditions provide a prediction that PT train Api Indonesia can continue living in the future in providing rail transport services for the Indonesian community.